Depletion of Alloreactive T-Cells by Anti-CD137-Saporin Immunotoxin. Issue 6 (June 2015) - Lee, Sang C.; Seo, Kwang W.; Kim, Hye J.; Kang, Sang W.; Choi, Hye-Jeong; Kim, Ansuk; Kwon, Byoung S.; Cho, Hong R.; Kwon, Byungsuk
Depletion of alloreactive T-lymphocytes from allogeneic bone marrow tansplants may prevent graft-versus-host disease (GVHD) without impairing donor cell engraftment, immunity, and the graft-versus-leukemia (GVL) effect. Alloreactive T-cells may be identified by their expression, upon activation, of CD137, a costimulatory receptor and putative surrogate marker for antigen-specific effector T-cells. In this context, we tested the use of anti-CD137-saporin immunotoxin to selectively deplete mouse and human alloreactive T-cells. Anti-CD137 antibodies were internalized by cells within 4 h of binding to the cell surface CD137, and anti-CD137-saporin immunotoxin effectively killed polyclonally activated T-cells or antigen-stimulated T-cells. Transfer of donor T-cells after allodepletion with anti-CD137-saporin immunotoxin failed to induce any evident expression of GVHD; however, a significant GVL effect was observed. Targeting of CD137 with an immunotoxin was also effective in killing polyclonally activated or alloreactive human T-cells. Our results indicate that anti-CD137-saporin immunotoxin may be used to deplete alloreactive T-cells prior to bone marrow transplantation and thereby prevent GVHD and the relapse of leukemia.